Failure Risk of Short Dental Implants Under Immediate Loading: A Meta‐Analysis. Issue 7 (27th May 2021) - Wu, Hao; Shi, Quan; Huang, Yang; Chang, Ping; Huo, Na; Jiang, Yi; Wang, Juncheng
Abstract: Purpose: Currently, there is no clear clinical evidence that short implants are suitable for immediate loading. Therefore, this meta‐analysis aims to evaluate whether immediate loading increases the failure risk of short dental implants. Materials and Methods: This meta‐analysis was registered at PROSPERO (CRD 42020195890). PubMed, Embase, and Cochrane Library databases were searched to collect all clinical studies comparing the failure rates of short dental implants (<10 mm) and standard implants (≥10 mm) under the condition of immediate loading and studies comparing the failure rates of short dental implants under immediate loading versus early or delayed loading. All of the clinical studies with available relevant data were eligible for inclusion. The Cochrane Risk of Bias tool was adopted to evaluate the risk of bias for the randomized controlled trial (RCT), while Newcastle‐Ottawa Quality Assessment Scale (NOS) was used for the observational studies (OS). The OR value of each included study and its 95% CI were pooled to estimate the failure risk of short dental implants under immediate loading. The heterogeneity among studies was evaluated through Cochran's Q test and I 2 . Results: Seventeen studies, 5 RCTs and 12 OS studies, with a total of 2461 dental implants were analyzed. Four of the RCT studies were of low risk of bias and one was of unclear risk, while all of the OS studies were of moderate or high quality. Compared with standard implants, short implants did not have an increased failure risk under immediate loading (OR: 1.38, 95% CI: 0.67‐2.84, p = 0.997, fixed model). In addition, the OR value of implant failure for short implants under immediate loading compared to that for short implants under early or delayed loading was 1.22 (95% CI: 0.33‐4.55, p = 0.104, random model), which was also not significantly different. Conclusions: There is not enough evidence to show that short dental implants under immediate loading may have higher implant failure risk compared to standard implants under immediate loading and short implants under early or delayed loading. Therefore, an immediate loading protocol may not increase the failure risk of short dental implants.